Simple and efficient numerical tools for the analysis of parachutes. Issue 5 (1st July 2014) - Flores, Roberto; Ortega, Enrique; Onate, Eugenio
Abstract : Purpose: – The purpose of this paper is to describe a set of simple yet effective, numerical method for the design and evaluation of parachute-payload system. The developments include a coupled fluid-structural solver for unsteady simulations of ram-air type parachutes. The main features of the computational tools are described and several numerical examples are provided to illustrate the performance and capabilities of the technique. Design/methodology/approach: – For an efficient solution of the aerodynamic problem, an unsteady panel method has been chosen exploiting the fact that large areas of separated flow are not expected under nominal flight conditions of ram-air parachutes. A dynamic explicit finite element solver is used for the structure. This approach yields a robust solution even when highly nonlinear effects due to large displacements and material response are present. The numerical results show considerable accuracy and robustness. Findings: – A simple and effective numerical tool for the analysis of parachutes has been developed. Originality/value: – An analysis code has been developed which addresses the needs of ram-air parachute designers. The software delivers reasonably accurate results in a short time using modest hardware. It can therefore assist the design process, which nowadays relies on empirical methods.